The impact of using chickpea flour and dried carp fish powder on pizza quality. - Hossam S El-Beltagi; Naglaa A El-Senousi; Zeinab A Ali; Azza A Omran (PLoS ONE)
Pizza being the most popular food worldwide, quality and sensory appeal are important considerations during its modification effort. This study was aimed to evaluate the quality of pizza made using two different sources of proteins, chickpea (Cicer arietinum) flour and dried carp fish powder (Cyprinus carpio). Analysis indicated nutrients richness specificity of chickpea flour (higher fiber, energy, iron, zinc, linoleic acid and total nonessential amino acids) and dried carp fish powder (higher contents of protein, fats, ash, oleic acid and total essential amino acids) complementing wheat flour to enhance nutritional value of pizza. Total plate count and thiobarbituric acid were increased (P<0.05) in dried carp fish powder after 45 days of storage, but no Coliform were detected. Wheat flour was substituted with 5, 7.5 and 10% chickpea flour or dried carp fish powder and chemical, textural, sensory and storage evaluation parameters of in pizza were investigated. Dried carp fish powder increased (P<0.05) contents of protein, ash, fats, zinc and protein digestibility of pizza. Chickpea flour increased iron and zinc contents of the pizza. Water activity (aw) was decreased in fish powder and chickpea pizza. Pizza firmness and gumminess were significantly (p<0.05) increased at every level of protein source, but cohesiveness was decreased with 10% chickpea flour. Pizza chewiness was the same (P>0.05) across the levels of two protein sources. Springiness was decreased (P<0.05) with high level (10%) dried fish powder and low/intermediate level of chickpea flour. Chickpea and dried carp fish incorporation up to 7.50% in pizza at the expense of wheat flour had no effect (P>0.05) on all sensorial parameters except for odor values. The results could be useful in utilization of chickpea flour and carp fish powder in designing nutritious pizza for consumers.